By-Laws, Rules and Regulations : 1999. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This paper discusses 56th issue of the By-Laws and Rules and Regulations of the IMF. It highlights that the principal office of the IMF shall be located within the metropolitan area of Washington, DC. The Executive Board may establish and maintain agencies or branch offices at any place in the territories of other members, whenever it is necessary to do so to facilitate the efficient conduct of the business of the IMF. The Board of Governors shall hold regular meetings, which shall be at annual intervals unless the Board of Governors decides otherwise.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet